Social Media Marketing's Effect on Purchase Intentions for Puma: Mediation by Brand Image, Awareness, and Equity - Rolando, Benediktus; Sunara, Nathaniel Toby (Forum Kerjasama Pendidikan Tinggi, 2024)
The rapid growth of social media platforms has revolutionized how brands interact with their customers. This study aims to quantitatively investigate the impact of social media marketing activities (SMMA) on customers' purchase intention for the Puma apparel brand in Indonesia, with brand image, brand awareness, and brand equity as mediating factors. The study first examines Puma’s promotional efforts across social media platforms such as Facebook, Twitter, Instagram, and YouTube. Using Structural Equation Modeling (SEM) with SmartPLS 3 software, the research evaluates the effectiveness of Puma's social media marketing activities in enhancing brand awareness, brand image, and brand equity. The data was collected from a sample of 93 Indonesian university students via an online survey. The findings reveal that social media marketing activities have a limited impact on brand awareness, brand equity, and brand image, with R-square values of 0.184, 0.303, and 0.279, respectively. Furthermore, we found that social media marketing activities have a positive and significant impact on brand awareness (P = 0.000, T = 4.591), brand image (P = 0.000, T = 6.596), and brand equity (P = 0.000, T = 6.027), which in turn significantly influence customers' purchase intention. Brand awareness and brand image are shown to positively affect purchase intention (P = 0.004, T = 2.056 for brand awareness; P = 0.001, T = 3.427 for brand image), while brand equity (P = 0.000, T = 4.325) also significantly contributes to purchase intention. However, the relationship between brand awareness and brand equity was not statistically significant (P = 0.482, T = 0.703). The R-square results further indicate a moderate impact of the independent variables on purchase intention (R² = 0.566). These findings provide valuable insights for brand managers and marketing professionals in the apparel industry, emphasizing the strategic use of social media marketing to drive customer engagement, build brand loyalty, and ultimately influence purchasing decisions.